SPEAKING ABILITY IN ENGLISH PRONUNCIATION IN THE FORM OF A PHONETIC TRANSCRIPTION - Lindawati, Ni Putu (LITERA : Jurnal Bahasa Dan Sastra, 2021)
ABSTRACTSpeaking is one of the language skills that have a crucial function in performing humanlanguage ability. Together with the other three language skills, the speaking domain could beincreased continuously, and this stage could be done in the classroom learning system. In theEnglish level of pronunciation, the students often face an obstacle in doing it. The difficultpronunciation and the interference of first language, make their performances are not in thebest stage. Sometimes, this could lead the students reluctant to try speaking when they have topractice in class. Increasing speaking skills, it is required specific techniques and strategies.The most important one is they need to have a sustainable practice to increase their skillsgradually and significantly.Keyword: Speaking, pronunciation, first language, a specific strategy, practiceABSTRAKBerbicara merupakan salah satu keterampilan berbahasa yang memiliki fungsi penting dalammenampilkan kemampuan berbahasa manusia. Bersama dengan ketiga keterampilan bahasalainnya, ranah berbicara dapat ditingkatkan secara terus menerus, dan tahap ini dapatdilakukan dalam sistem pembelajaran di kelas. Dalam pelafalan bahasa Inggris, siswaseringkali menghadapi kendala dalam melakukannya. Pelafalan yang sulit dan gangguanbahasa pertama, membuat penampilan mereka tidak dalam tahap terbaik. Terkadang, hal inidapat menyebabkan siswa enggan mencoba berbicara ketika harus berlatih di kelas. Untukmeningkatkan keterampilan berbicara, diperlukan teknik dan strategi khusus. Yang palingpenting adalah mereka perlu memiliki praktik yang berkelanjutan untuk meningkatkanketerampilan mereka secara bertahap dan signifikan.Kata kunci: Berbicara, pengucapan, bahasa pertama, strategi tertentu, latihan